Memorandum : Accidents to cyclists ; Situation in Spain - Tewson, Vincent
011-0116-001 HVT/CB. Secretary's To all Members of the Finance and General Purposes Committee. 18th March, 1937 Dear Sir, Accidents to Cyclists At the meeting of the Finance and Genoral Purposes Committee which is to be held on Monday next - notice of which you will already have received - one item on the agenda will be the consideration of a Memorandum on Accidents to Cyclists. I forwarding a copy of the Memorandum, which has been sent out to Affiliated Unions and Trades Councils. It has not yet been possible to peruse all the replies, but I thought I would let you have a copy of the first Draft, in order that you say examine it in detail. At the Committee Meeting on Monday, a further document will be submitted, setting out any further suggestions which may arise as the result of replies by our affiliated Unions and Trades Councils. Situation in Spain After consultation with representatives of the Labour Party Executive and of the Party in the House, it has been decided that a Deputation should wait upon Mr. Eden at the House of Commons at 5.30 p.m. on Monday next. It Is proposed the Deputation should consist of members of the Finance Committee. Before going over to the House it will be possible for a preliminary discussion to take place. The purpose of the deputation is to deal with the alleged infringement of the Non-intervention Agreement, and to impress the Foreign Secretary with our anxiety in regard to the position. Probably, therefore, you would msake the necessary arrangements to enable you to attend on this deputation. Yours sincerely, Assistant Secretary. Memorandum. 292/946/11/116